Genesis of Universals in Prasastapada and Genesis of the Principia Prima and Universals in Aristotle - Tola, Fernando; Dragonetti, Carmen (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
In this article the authors offer a new instance of their thesis concerning the frequent thematic coincidences between Indian and Western philosophies, which they developed in their books On the Myth of the Opposition between Indian Thought and Western Philosophy (Hildesheim: Olms Verlag, 2004), reviewed by Ernst Steinkellner (in WZKS Band XLVIII 2004, 224-225); and Yoga: Un Camino Místico Universal (Barcelona: Editorial Kairós, 2006). This thesis hints to what could be called the globality of philosophical thought. Prasastapada, in Prasastapadabhasya (also called Padarthadharmasngraha), Book V: Samanyapadarthanirupana, gives two descriptions of the genesis of universals. He first describes in an abstract and concise way the process of arising of any samanya, «universal», and then he explains in a more concrete way the arising of the inferior and superior universal (satta), through the reiteration of the perception of objects that offer similar attributes and the intervention of the memory of past perceptions. Aristotle (4AD), in Analytica Posteriora (Book II, Chapter XIX), and the commentary of Themistius (c. 317-387) explain the manner by which universal principles or the premises of the demonstration (principia prima) are apprehended. The authors of this paper show how Aristotle’s and Themistius’ descriptions of the genesis of the principia prima and of universals agree in an amazing way with Prasastapadas concerning universals.